SELF-REGULATED LEARNING AND ACADEMIC STRESS IN MEDICAL SCHOOL: ARE THEY RELATED? SELF-REGULATED LEARNING AND ACADEMIC STRESS - Alister Garcia Himawan; Yoanita Widjaja (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: During the transition to higher education, many students experience stress due to the process of adapting to a new educational and social environment. Excessive or negative stress may lead to physical and psychological reactions, such as persistent lack of energy, loss of appetite, headaches, gastrointestinal problems or signs of emotional distress. It may be theorized that students who are more proficient at self-regulated learning would display problem solving coping strategies when dealing with academic demands, therefore reducing perceived levels of academic stress. This study aims to explore any statistically significant relationship between the levels of self-regulated learning and academic stress. Methods: The study is a cross-sectional, observational analytic study with a sample size of 222 respondents obtained from medical students at Tarumanagara University.  Results: The majority of respondents (80.6%) experienced moderate academic stress, although statistical analysis shows no statistically significant relationship between self-regulated learning and academic stress.  Conclusions: Further research should be done on the cross-cultural applicability of the concepts of self-regulated learning. Medical educational institutions should implement learning and lecture strategies that promote emotional and mental wellness among students as an approach to reduce the levels of academic stress.